The attitude, intention, and related factors of purchasing antibiotics without prescription: a survey in Vietnam - Thi Le, Ngoc Minh; Dang, Khanh Duy; Nguyen, Hung Phuc (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The abuse of antibiotics is a global problem, and the form of abuse varies among different countries and cultures. The study explored antibiotic self-medication attitudes and intentions to use antibiotics among the public in Can Tho City, Vietnam. Study design. Questionnaire survey on a sample of volunteers.Methods. Between February and August 2023, a paper-based questionnaire survey was conducted among the public in 4 districts of Can Tho City, Vietnam. The data was analyzed with SPSS version 20.0. Descriptive and analytical statistics using multivariate logistic regression analysis were performed to identify the factors associated with antibiotic self-medication. Results. Of the 414 people interviewed, 56% were female, and the majority were aged 30-45 (48.49%). People with a university professional degree accounted for 39.4%, of whom 10.6% were the medical staff. The overall average score on attitude was 4.43±1.589 (on a 10-point scale), and 85.7% of people had inappropriate attitudes. Average scores of the indicators (a) Positive attitude towards the use of non-prescription antibiotics, (b) Negative attitude towards the use of non-prescription antibiotics, (c) Subjective norms, (d) Perceived behavioral control, and (e) Intention to purchase antibiotics without a prescription were 3.73±0.043, 2.29±0.944, 4.36±1.45, 3.4±1.027, and 3.63±1.145, respectively. The rate of people intending to buy non-prescribed antibiotics was 63.8%. Factors related to people’s intention to purchase antibiotics without a prescription included place of residence, education level, occupation, and income. All three factors, attitude, subjective norm, and perceived behavioral control, impacted the intention to buy non-prescription antibiotics, of which the subjective norm factor had the most substantial impact.Conclusions. The rate of people having incorrect attitudes about antibiotics, leading to the intention to buy antibiotics without a prescription, was relatively high. Factors affecting people’s intention to purchase non-prescribed antibiotics included factors related to the impact of other people around them and factors originating from themselves.